Inclusive Development: The Contribution of the Next-Generation Social Welfare Information System to the Accountability of Village Assistance Programs - Diva Margareta; Iskandar Zulkarnaen (Athena: Journal of Social, Culture and Society, 2026)
Inclusive development is the primary objective of the village assistance program. The Next Generation Social Welfare Information System (SIKS-NG) is a solution for improving the accountability of the village assistance program. This study aims to describe the contribution of SIKS -NG in improving the accountability of the village assistance program based on public accountability theory Mahmudi, 2019, regarding the dimensions of accountability that must be fulfilled by public sector organizations, namely Legal and Integrity Accountability, Managerial Accountability, Program Accountability, Policy Accountability, and Financial Accountability. The research method employed a qualitative approach with data collection techniques through interviews and observations, with the main informants being staff from the Social Affairs Office (Integrated Referral Service System) of Cirebon Regency and officers from the Social Welfare Center (PUSKESOS) of Palimanan Timur Village. The research results indicate that SIKS-NG can enhance the accountability of village assistance programs by providing accurate and transparent data, as well as increasing community participation in decision-making. Therefore, as stipulated in Regulation of the Minister of Social Affairs of the Republic of Indonesia No. 3 of 2025 regarding the updating and use of the National Single Social and Economic Data System for social assistance, social empowerment, and social welfare programs, this study aims to promote inclusive development in Palimanan Timur Village. It is hoped that a digital-based system designed to manage the National Social and Economic Single Data System (DTSEN) can be more transparent, accurate, and efficient in its implementation for the community.